Commentary – bridging the research and practice gap in autism: The importance of creating research partnerships with schools. (May 2013) - Parsons, Sarah; Charman, Tony; Faulkner, Rachel; Ragan, Jude; Wallace, Simon; Wittemeyer, Kerstin
While the last 10 years have seen a significant increase in research published on early intervention and autism, there is a persistent disconnect between educational research and practice. Governments have invested significant funds in autism education, and a range of approaches have been implemented in schools, but there is limited research exploring whether these educational strategies are effective and a lack of involvement of teaching professionals in the research. Given that the majority of children and young people with autism spend most of their time in school and not in early or specialised intervention programmes, there is a compelling need to conduct better educational research and implement educational interventions in schools. We argue that building collaborative partnerships between researchers and school practitioners is central to achieving improved understanding of, and outcomes for, pupils on the autism spectrum. This commentary offers perspectives from teachers about their experiences of, and priorities for, research, and also presents a model of collaboration between autism school practitioners and researchers, which could support a more integrated approach to research. We reflect on the strengths and challenges of this as well as outcomes achieved so far.